Total Exposure Health An Introduction - Phillips, Kirk; Yamamoto, Dirk P.; Racz, LeeAnn (Taylor & Francis, 2020)
This book provides a comprehensive overview of the concept of "Total Exposure Health" and presents details on subject areas which make up the framework. It provides in-depth coverage of the science and technology supporting exposure and risk assessment. This includes advances in toxicology and the "-omics" as well as new techniques for exposure assessment. The book concludes with a discussion on bioethics implications, including ethical considerations related to genetic testing.